Aeromonas dhakensis, an Increasingly Recognized Human Pathogen - Chen, Po-Lin; Lamy, Brigitte; Ko, Wen-Chien (Frontiers in Microbiology, 2016)
Aeromonas dhakensis was first isolated from children with diarrhea in Dhaka, Bangladesh and described in 2002. In the past decade, increasing evidence indicate this species is widely distributed in the environment and can cause a variety of infections both in human and animals, especially in coastal areas. A. dhakensis is often misidentified as A. hydrophila, A. veronii or A. caviae by commercial phenotypic tests in the clinical laboratory. Correct identification relies on molecular methods. Increasingly used matrix-assisted laser desorption ionization-time of flight mass spectrometry (MALDI-TOF MS) may be able to identify Aeromonas specie rapidly and accurately. A. dhakensis has shown its potent virulence in different animal models and clinical infections. Although several virulence factors had been reported, no single mechanism is conclusive. Characteristically A. dhakensis is the principal species causing soft tissue infection and bacteremia, especially among patients with liver cirrhosis or malignancy. Of note, A. dhakensis bacteremia is more lethal than bacteremia due to other Aeromonas species. The role of this species in gastroenteritis remains controversial. Third generation cephalosporins and carbapenems should be used cautiously in the treatment of severe A. dhakensis infection due to the presence of AmpC β-lactamase and metallo-β-lactamase genes, and optimal regimens may be cefepime or fluoroquinolones. Studies of bacterial virulence factors and associated host responses may provide the chance to understand the heterogeneous virulence between species. The hypothesis A. dhakensis with varied geographic prevalence and enhanced virulence that compared to other Aeromonas species warrants more investigations.